Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania

Esterification of renewable levulinic acid to ethyl levulinate biodiesel catalyzed by highly active and reusable desilicated H-ZSM-5 - Nandiwale, Kakasaheb Y.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Bokade, Vijay V. (Journal of Chemical Technology and Biotechnology, 2014)
BACKGROUNDIn the near future, fossil fuel will have limitations in terms of availability and also great concerns over its environmental impact. New routes and related technologies based on renewable feedstocks can overcome most of these problems associated with fossil fuel. Among current biodiesel sources, ethyl levulinate (EL) biodiesel obtained from catalytic esterification of renewable levulinic acid (LA) with ethanol has received a great deal of attention. The use of desilicated H-ZSM-5 (DH-ZSM-5) as heterogeneous acid catalyst for EL biodiesel production in a closed system (under autogeneous pressure) was studied. RESULTSThe effect of reaction parameters such as ethanol to LA molar ratio (4:1 to 10:1), catalyst to LA ratio (0.10-0.25), speed of agitation (100-400rpm), particle size (53-355 mu m), reaction temperature (363-403K) and reaction time (7h) was investigated to maximize LA conversion. CONCLUSIONLevulinic acid conversion reached 95% over DH-ZSM-5 and the catalyst was reusable for up to six cycles. This LA conversion and the catalyst reusability values are higher than others reported in the literature. A pseudo-homogeneous (P-H) kinetic model indicated that reaction rate constants increased with increasing molar ratio, catalyst to LA ratio and reaction temperature. The activation energy decreased from 73.14 to 21.08 kJ mol(-1) when increasing the catalyst to LA ratio from 0.10 to 0.25, which implies a kinetically controlled reaction. (c) 2013 Society of Chemical Industry
Keywords: desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

Epoxidation of karanja (Millettia pinnata) oil methyl esters in the presence of hydrogen peroxide over a simple niobium-containing catalyst - Scotti, Nicola; Ravasio, Nicoletta; Evangelisti, Claudio; Psaro, Rinaldo; Penso, Michele; Niphadkar, Prashant S.; Bokade, Vijay V.; Guidotti, Matteo (Catalysts, 2019)
The synthesis, characterization and catalytic performance of a conceptually simple, novel NbOx-SiO2 catalyst are here described. The niobium(V)-silica catalyst was prepared starting from cheap and viable reactants, by alkaline deposition of NH4Nb(C2O4)(2)H2O in the presence of fructose as a stabilizer and subsequent calcination. The NbOx-SiO2 solid (0.95 Nb wt.%) was tested in the liquid-phase epoxidation with aqueous hydrogen peroxide of methyl oleate, as a model substrate. It was then tested in the epoxidation of a mixture of methyl esters (FAMEs) obtained by transesterification with methanol and purification of karanja oil, extracted from the autochthonous Indian variety of Millettia pinnata tree. The catalyst showed a promising performance in terms of methyl oleate conversion (up to 75%) and selectivity to epoxide (up to 82%). It was then tested on the FAME mixture from karanja oil, where interesting conversion values were attained (up to 70%), although with lower selectivities and yields to the mixture of desired epoxidized FAMEs. The solid withstood four catalytic cycles overall, during which a non-negligible surface reorganization of the Nb(V) sites was observed. However, this restructuring did not negatively affect the performance of the catalysts in terms of conversion or selectivity.
Keywords: epoxidation; fatty acid methyl esters; heterogeneous catalysis; Hydrogen peroxide; karanja oil; mesoporous silica catalyst; Millettia pinnata; niobium catalysts

Equilibrium adsorption of nitrogen, oxygen, and argon on silver-exchanged hierarchical ETS-10 - Shrotri, Aadesh R.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Chemical and Engineering Data, 2023)
Silver-exchanged hierarchical ETS-10(Ag-H-ETS-10) was synthesizedusing Ag+ exchange with hierarchical Engelhard titanosilicate(H-ETS-10) using silver nitrate solution. The physical propertiesof the adsorbent were analyzed using X-ray diffraction (XRD), BETsurface area, nitrogen adsorption-desorption, pore volume,energy dispersive spectroscopy (EDS), and high resolution-transmissionelectron microscopy (HR-TEM). N-2 physisorption data confirmedthat a micro-mesoporous (bimodal) structure was created in the Ag-H-ETS-10.The equilibrium adsorbent data of pure gases N-2, O-2, and Ar were investigated in the temperature range from 288to 318 K up to 10 bar. The equilibrium adsorption capacity of Ag-H-ETS-10was found to be 1.12 mmol g(-1) for N-2,0.87 mmol g(-1) for O-2, and 1.09 mmol g(-1) for Ar at 298 K and & SIM;10 bar. & SIM;20% higheradsorption capacity was found for N-2 and Ar in Ag-H-ETS-10compared to Ag-ETS-10. The higher sorption capacity was attributedto the formation of a bimodal structure and & pi;-complexation interactionby the Ag cation, which allows a multilayer of N-2 and Armolecules. The Sips isotherm model was well fitted for the Ag-H-ETS-10experimental data among Langmuir, Freundlich, Toth, and Temkin models.The measured equilibrium adsorption data for Ag-H-ETS-10 can be usefulfor the O-2 purification process.

Effect of CTMABr/SiO2 molar ratio in synthesis of micro-mesoporous ZSM-5 composite and its application in 5-EMF (biofuel additive) formation - Manal, Prajakta N.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Bokade, Vijay V. (Environmental Progress and Sustainable Energy, 2024)
Synthesis of micro-mesoporous zeolite composite with optimum micro and mesoporosity is an emerging research area due to its wide applications, especially in bulk chemical or biomass transformations. It offers advantages in preserving zeolite crystallinity, creating mesoporosity and converting bulky molecules into valuable products. This work presents the process of preparing bimodal micro-mesoporous ZSM-5 using dual templates (CTMABr and TPABr). XRD, N2 adsorption-desorption, SEM, TEM, Si-29, and Al-27 NMR were used to analyze the two-dimensional micro-mesoporous ZSM-5. One-step synthesis of bimodal micro-mesoporous ZSM-5 features dual micro/mesoporosity by a marginal decrease in the crystallinity (71%). Micro-mesoporous ZSM-5 composite was found to be dependent on the optimum CTMABr/SiO2 molar ratio of 0.04 to 0.06. The micro-mesoporous ZSM-5 zeolite composite was evaluated for cascade synthesis of 5-EMF (methoxymethyl furfural- biofuel additive) from fructose and exhibited a five fold increase in 5-EMF yield to 24.2% as compared with parent ZSM-5 (4.6%).
Keywords: fructose; methoxymethyl furfural-biofuel additive; micro-meso composite; ZSM-5